The story line of the studies on airborne contamination in museums and historical libraries related to biodeterioration and health of operators and visitors - Albertini, Roberto; Mohieldin Mahgoub Ibrahim, Mostafa; Coluccia, Alessia; Colucci, Maria Eugenia; Affanni , Paola; Zoni , Roberta; Veronesi, Licia; Pasquariello, Giovanna; Pasquarella, Cesira (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: In cultural-heritage-related indoor environments, biological particles represent a hazard not only for cultural property, but also for operators and visitors. The effectiveness of conservation for indoor cultural heritage and the health of operators and visitors derives from appropriate control and management. This study aimed to analyse the scientific community’s activity on airborne contamination in indoor cultural heritage related to biological risks for artifacts, staff, and users to sensibilize insiders and decision makers about the importance of knowledge on this topic. Methods: We searched in Scopus for articles reporting the words “libraries or museums and air/airborne contamination” in the article title or abstract or keywords. Articles written in all languages were considered and crosschecked with related issues. Results: A total of 206 documents concerning the biodeterioration of libraries, or museums have been found since 1977 of which 155 were original articles. United States, Italy, Poland, China and United Kingdom were the countries most involved in this research. A total of 47 documents investigated microbial air/airborne contamination in libraries, or museums, and Italy appeared in the first five countries, with the publication of some papers proposing multidisciplinary approaches for sampling and analysis of data. Conclusions: Our study can represent a contribution towards the studies on biological air quality of indoor cultural heritage for libraries, and museums. It is necessary to promote and support the research on this topic with a multidisciplinary and One Health approach, considering that a healthy environment for humans is equally healthy for artworks.